Sosialisasi Aspek-aspek Mu’amalah dalam Ekonomi Islam di Desa Jatimekar Kecamatan Jatiluhur - Sucipto, Imam; Rahmawati, Harkit (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Human life requires a legal order, in Islam the law is sourced from the Qur'an, al-Hadith, and ijtihad, then the product of ijtihad is fiqh. Jurisprudence has covered all the institutions of individual and community life, whether economic, social, state politics, and others. The scholars never stop studying all the phenomena and problems mentioned above, especially the problem of mu'amalah, because mu'amalah is considered important because it is related to human interaction with other humans. The people of Jatimkar village, Jatiluhur purwakarta, are mostly fishermen, which automatically has a lot of economic interactions in order to fulfill their daily needs. The purpose of this PKM is to provide socialization and understanding to the people of Jatimkar Village, Jatiluhur District regarding the aspects of mu'amalah in Islamic economics, so that the community knows this comprehensively so that it has implications for muamalah activities correctly in accordance with the concept of sharia economics. The method used in this PKM program uses the method of socialization and interaction. The PKM activity on the socialization of mu'amalah aspects in Islamic economics in Jatimkar Village, Jatiluhur District, Purwakarta Regency has technically been successfully carried out. The people of Jatiluhur Village, Jatiluhur Purwakarta, already know the aspects of mu'amalah in Islamic economics, both mu'amalah al-Iqtishady and mu'amalah al-Maliyah correctly. And people can apply mu'amalah aspects in everyday life. So that it is hoped that the community meeting of the people of Jatimkar Village, Jatiluhur District, Purwakarta Regency is in accordance with the concept of Islamic economics.